Vertical distribution of 137Cs in grassland soils disturbed by moles (Talpa europaea L.). (April 2018) - Ramzaev, V.; Barkovsky, A.
Abstract: Activity of biota is one of the factors influencing vertical migration of radionuclides deposited from the atmosphere onto the ground surface. The goal of this work was to study the vertical distribution of 137 Cs in grassland soils disturbed by moles ( Talpa europaea L.) in comparison with undisturbed grassland soils. Field observations and soil sampling were carried out in the areas of eight settlements in the Klintsovskiy, Krasnogorskiy and Novozybkovskiy districts of the Bryansk region, Russia in six years during the period 1999–2016. The study sites had been heavily contaminated by Chernobyl fallout in 1986. Activity of 137 Cs in soil samples was determined by γ-ray spectrometry. 137 Cs surface ground contamination levels at the studied plots (n = 17) ranged from 327 kBq m −2 to 2360 kBq m −2 with a mean of 1000 kBq m −2 and a median of 700 kBq m −2 . The position of the 137 Cs migration centre in the soil in 2010–2016 was significantly (the Mann-Whitney U test, P < .01) deeper at mole-disturbed plots (median = 5.99 cm or 6.64 g cm −2, n = 6) compared to the undisturbed ones (median = 2.48 cm or 2.35 g cm −2, n = 6). The 137 Cs migration rate at mole-disturbed plots (median = 0.26 g cm −2  y −1, mean = 0.31 g cm −2  y −1 ) was significantly higher (by a factor of 3) than at undisturbed plots (median = 0.08 g cm −2  y −1, mean = 0.10 g cm −2  y −1 ). The difference in the migration rates between the mole-disturbed and undisturbed plots (median = 0.18 g cm −2  y −1, mean = 0.21 g cm −2  y −1 ) reasonably corresponded to the mass of soil that might be ejected by moles per unit area per year. The results of this study indicate that the burrowing activity of moles has increased vertical migration of Chernobyl-derived radiocaesium in the grassland soils. Graphical abstract: Highlights: Vertical distributions of Chernobyl 137 Cs in soils in 17 grasslands are presented. Mean migration depths of 137 Cs at mole-disturbed and control plots were determined. The burrowing activity of moles increased vertical migration of 137 Cs in the soils.